Evaluation of Antifungal Efficacy of Vitex Negundo against Candida Albicans and Candida Glabrata: An In Vitro Study - Ravi, Ashwini; V, Vasanthi; Krishnan, Rajkumar; S, Savithri; Padmanabhan, Gopikrishna; Sathiyamoorthy, Mounika (Journal of Nepalese Prosthodontic Society, 2026)
Introduction: Oral candidiasis is an opportunistic disease commonly caused by Candida albicans. Immunocompromised patients are more prone to candidal opportunistic infections. Vitex negundo, is a well-recognised medicinal plant with a wide range of pharmacological properties, including anti-inflammatory, antioxidant, and antimicrobial activity. The present study aimed to evaluate the antifungal efficacy of leaves of Vitex negundo against oral candidal species. Methods: Leaves of Vitex negundo were procured, dried and ground into fine powder. Dimethyl sulfoxide was used as the solvent. The antifungal efficacy of ethanolic leaf extract was evaluated at a concentration of 50mg/ml. The zone of inhibition was evaluated to study the antifungal efficacy of Vitex negundo against Candida albicans and Candida glabrata. Results: The zone of inhibition against C. albicans and C. glabrata was 25 ± 0.8 mm and 29 ± 0.9 mm, respectively. Clotrimazole (positive control) produced a zone of inhibition measuring 30 ± 0.5 mm against C. albicans and 30.5 ± 0.7 mm against C. glabrata. Conclusion: The present in vitro study demonstrated the antifungal efficacy of Vitex negundo against Candida albicans and Candida glabrata. However, further clinical studies are necessary to establish the efficacy, safety, and sustainability as an alternative to conventional antifungal agents.